Accelerated chemical stability data of O/W fluid emulsions containing the extract of Trichilia catigua Adr. Juss (and) Ptychopetalum olacoides Bentham - Baby, André Rolim; Migliato, Ketylin Fernanda [UNESP]; Maciel, Carolina Penteado Moraes; Zague, Vivian; Pinto, Claudinéia Aparecida Sales De Oliveira; Salgado, Hérida Regina Nunes [UNESP]; Kaneko, Telma Mary; Velasco, Maria Valéria Robles (Divisão de Biblioteca e Documentação do Conjunto das Químicas da Universidade de São Paulo, 2007)
Development of topical dosage forms requires physical, physicochemical and chemical assays that provide, as soon as possible, the formulation with the best stability profiles. This study evaluated the stability of O/W fluid emulsions, by total flavonoids determination, expressed in rutin, containing the standardized extract of Trichilia catigua Adr. Juss (and) Ptychopetalum olacoides Bentham. Samples were evaluated for 90 days stored at 24.0 ± 2.0 ºC, 5.0 ± 0.5 ºC and 40.0 ± 0.5 ºC, following a protocol for the assessment of accelerated chemical stability assay, also known as Normal Stability Test. A sensitive UV-spectrophotometric method at 361.0 nm was previously validated for the determination of the active substance. By Normal Stability Test, the O/W fluid emulsions presented acceptable chemical stability, for at least 90 days, when the samples were stored at 24.0 ± 2.0 ºC and 5.0 ± 0.5 ºC. The storage condition at 40.0 ± 0.5 ºC has accelerated the degradation process of the total flavonoids, consequently, those O/W emulsions containing this kind of natural active substance or a similar preparation must not be stored at elevated temperatures.

O desenvolvimento de formas farmacêuticas tópicas necessita ensaios físicos, físico-químicos e químicos que selecionem rapidamente a formulação de melhor desempenho de estabilidade. Este estudo avaliou a estabilidade de emulsões O/A fluidas, por meio da determinação de flavonóides totais, expressos em rutina, contendo o extrato padronizado de Trichilia catigua Adr. Juss (e) Ptychopetalum olacoides Bentham. As amostras foram armazenadas a 24,0 ± 2,0 ºC; 5,0 ± 0,5 ºC e 40,0 ± 0,5 ºC durante 90 dias e foram avaliadas segundo o protocolo para a determinação da estabilidade acelerada, conhecida como Teste de Estabilidade Normal. A quantificação da substância ativa foi determinada por espectrofotometria na região do ultravioleta a 361,0 nm, previamente validado. Após os ensaios de estabilidade, as emulsões O/A fluidas apresentaram estabilidade adequada, pelo menos, no período de 90 dias, quando armazenadas a 24,0 ± 2,0 ºC e 5,0 ± 0,5 ºC. A condição de armazenamento a 40,0 ± 0,5 ºC acelerou a cinética de degradação dos flavonóides totais, expressos em rutina, portanto, preparações possuindo esta categoria de substância ativa natural ou formulações similares não devem ser armazenadas em temperaturas elevadas.
Estabilidade química de emulsões O/A fluidas contendo o extrato de Trichilia catigua Adr. Juss (e) Ptychopetalum olacoides Bentham
Keywords: Stability test; Accelerated stability test; O/W emulsion; Trichilia catigua; Ptychopetalum olacoides; Rutin; Teste de estabilidade acelerada; Emulsão O/A; Trichilia catigua; Ptychopetalum olacoides; Rutina